Combined magnetic resonance imaging and spectroscopy in the assessment of high grade prostate carcinoma in patients with elevated PSA: A single-institution experience of 356 patients - Villeirs, Geert M.; De Meerleer, Gert O.; De Visschere, Pieter J.; Fonteyne, Valerie H.; Verbaeys, Antony C.; Oosterlinck, Willem (European journal of radiology, 2011)
To assess the ability of combined whole-prostate magnetic resonance imaging and magnetic resonance spectroscopy imaging (MRI + MRSI) to predict the presence or absence of high grade (Gleason 4 + 3 or higher) prostate carcinoma in men with elevated PSA. Between March 2002 and September 2007, 356 subjects (mean serum PSA 11.5 ng/ml, range 0.4–133.0 ng/ml) were examined with fast-T2-weighted magnetic resonance imaging (MRI) and 3D-magnetic resonance spectroscopy imaging (MRSI) on a 1.5 T scanner. Prostate cancer was histopathologically proven in 220 patients (41 with high grade and 179 with lower grade cancer) and non-evidence of cancer was determined after at least 12 months (mean 21 months) clinical follow-up in 136 subjects. The sensitivity, false positive rate, and negative predictive value of MRI + MRSI were calculated using histopathology and follow-up results as reference standard. MRI + MRSI had a significantly higher sensitivity for high grade tumors (92.7%) than for lower grade tumors (67.6%), and was false positive in only 7.4% of patients with non-evidence of prostate cancer. For exclusion of a high grade tumor, MRI + MRSI had a negative predictive value of 98.4%. MRI + MRSI holds great potential for predicting presence or absence of high grade tumors in men with elevated PSA. This can be important in the selection of patients for active surveillance, or in the decision to rebiopsy patients with prior negative biopsies.